Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.5114/aoms.2016.57884
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen excretion in pediatric lactose malabsorbers: relation to symptoms and the dose of lactose

Abstract: IntroductionLactose malabsorption arises from lactase deficiency and may lead to lactose intolerance – gastrointestinal symptoms after lactose ingestion. Occurrence and severity of the symptoms are influenced by many factors, including the dose of lactose and the intensity of its colonic fermentation to short chain fatty acids and gases.Material and methodsThe hydrogen breath test (HBT) after 30 g or 50 g of lactose was performed in 387 children. Further analysis included children who had a positive HBT result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The complex interaction of all these factors precludes calculation of compensatory adjustment of breath H 2 . The adjustment of breath H 2 concentrations for specific substrates or doses is not a standardized practice ( 42 ), and given that lactose dosing may even require adjustment for body weight ( 61 ), may not be a straightforward calculation. Although the current study showed lower lactose malabsorption with SM, differences in lactose digestion following SM should be investigated within the upper range of lactose content naturally occurring in SM, which may be more closely matched to CM.…”
Section: Discussionmentioning
confidence: 99%
“…The complex interaction of all these factors precludes calculation of compensatory adjustment of breath H 2 . The adjustment of breath H 2 concentrations for specific substrates or doses is not a standardized practice ( 42 ), and given that lactose dosing may even require adjustment for body weight ( 61 ), may not be a straightforward calculation. Although the current study showed lower lactose malabsorption with SM, differences in lactose digestion following SM should be investigated within the upper range of lactose content naturally occurring in SM, which may be more closely matched to CM.…”
Section: Discussionmentioning
confidence: 99%
“…Since the production of methane requires hydrogen metabolism, the hydrogen and methane concentrations can be simultaneously detected with the carbohydrate breath test. The lactulose hydrogen respiration test involves oral lactulose (non-absorbent sugar) to the cecum, fermentation with coliform bacteria to produce hydrogen and methane, absorption into the systemic circulation, and then exhalation to detect the concentration of hydrogen/methane in the breath; when the concentration of hydrogen/methane in the breath exceeds the baseline, a SIBO diagnosis can be reached[ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…16 A wide array of abdominal symptoms, such as abdominal pain, cramping, bloating, distention, nausea, flatulence, and loose stools or diarrhea, has been considered relevant symptoms in children and adolescents. 11,12,15 Here, we describe the development and validation of a self-administered symptom measurement questionnaire to assess the severity and the type of abdominal symptoms after the ingestion of a carbohydrate load in the pediatric population, the paediatric Carbohydrate Perception Questionnaire (pCPQ). A preliminary validation of this instrument has been reported elsewhere.…”
Section: Introductionmentioning
confidence: 99%
“…In the pediatric literature, the difficulty in data interpretation due to a lack of a validated symptom assessment tool has been acknowledged 11 . Symptoms following a carbohydrate challenge have been assessed by inviting the patient and/or their caregivers to report any undesignated symptom as it may arise, 12‐14 by recall of specific symptoms, 15 or by use of a generic pain questionnaire 13 or a questionnaire that was not validated for the pediatric population 16 . A wide array of abdominal symptoms, such as abdominal pain, cramping, bloating, distention, nausea, flatulence, and loose stools or diarrhea, has been considered relevant symptoms in children and adolescents 11,12,15 …”
Section: Introductionmentioning
confidence: 99%